2021
DOI: 10.3389/fvets.2021.716570
|View full text |Cite
|
Sign up to set email alerts
|

Panobinostat Effectively Increases Histone Acetylation and Alters Chromatin Accessibility Landscape in Canine Embryonic Fibroblasts but Does Not Enhance Cellular Reprogramming

Abstract: Robust and reproducible protocols to efficiently reprogram adult canine cells to induced pluripotent stem cells are still elusive. Somatic cell reprogramming requires global chromatin remodeling that is finely orchestrated spatially and temporally. Histone acetylation and deacetylation are key regulators of chromatin condensation, mediated by histone acetyltransferases and histone deacetylases (HDACs), respectively. HDAC inhibitors have been used to increase histone acetylation, chromatin accessibility, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Reprogramming vectors can be viral or nonviral, but viral vectors have been utilized in most canine reprogramming cases as summarized in Table 1 . To date, vectors used to generate ciPSCs have included unspecified retroviruses [ 2 , 15 , 21 , 33 , 35 ], lentiviruses [ 4 , 5 , 21 , 23 , 28 , 38 ], Sendai viruses [ 19 , 25 , 27 , 29 , 32 ], Venezuelan equine encephalitis (VEE) virus [ 24 ], and episomes [ 40 ].…”
Section: Current Methodologies For Cipsc Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reprogramming vectors can be viral or nonviral, but viral vectors have been utilized in most canine reprogramming cases as summarized in Table 1 . To date, vectors used to generate ciPSCs have included unspecified retroviruses [ 2 , 15 , 21 , 33 , 35 ], lentiviruses [ 4 , 5 , 21 , 23 , 28 , 38 ], Sendai viruses [ 19 , 25 , 27 , 29 , 32 ], Venezuelan equine encephalitis (VEE) virus [ 24 ], and episomes [ 40 ].…”
Section: Current Methodologies For Cipsc Productionmentioning
confidence: 99%
“…3 ) [ 52 , 53 ]. Global changes to chromatin accessibility, resulting from epigenetic changes to these loci, are a key determinant of successful cellular reprogramming [ 2 , 28 , 32 , 53 , 54 ] ( Fig. 3 ).…”
Section: Addressing Current Limitations In Reprogramming Canine Cells...mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of iPSC generation has been further pursued in dogs. For instance, Moshref et al ( 99 ) hypothesized that HDAC inhibitors would increase chromatin accessibility and facilitate reprogramming of adult canine cells. These authors found that neither valproic acid nor sodium butyrate effectively inhibited canine HDAC.…”
Section: “Step-by-step” Approach For Generating Ipscs In Companion An...mentioning
confidence: 99%
“…These authors found that neither valproic acid nor sodium butyrate effectively inhibited canine HDAC. On the other hand, panobinostat, another HDAC inhibitor, significantly increased histone acetylation and improved chromatin accessibility but without evidence of increased efficiency of generating iPSCs ( 99 ). Furthermore, Kimura et al found that a cocktail of small molecules including some of the inhibitors mentioned (ROCK inhibitor, MEK inhibitor, GSK3b inhibitor, TGFβ antagonist, forskolin, and ascorbic acid) contributed to efficient generation of canine iPSCs ( 92 ).…”
Section: “Step-by-step” Approach For Generating Ipscs In Companion An...mentioning
confidence: 99%